Study on the Dynamic Characteristic of Planetary Gear Transmission System with Tooth-breaking - Yang Rui; Zhou Jianxing; Jiang Hong; Adayi·Xieeryazidan (Jixie chuandong, 2018)
In order to explore the dynamic characteristics of planetary gear transmission system after a failure,combining with the Hertz contact theory and gears excitation,the planetary gear transmission system model in consideration of the contact characteristics of the tooth surface is established. And three tooth-breaking fault factors are introduced into the model,including the planetary wheel,ring gear,and sun gear. The working process of the transmission system under different fault factors are respectively simulated the and its dynamic characteristics are studied by analyzing the dynamic loading spectrum and floating trajectory. Come to conclusion,when the tooth-breaking fault occurs on the planetary gear and the sun wheel,the fault cycle is shorter and has bigger effect on the system than that occurs on the inner gear ring. There is correspondence between the fault frequency and frequency of amplitude of low frequency area in the spectrum. The tooth-breaking fault of the sun wheel makes the radius of center floating trajectory of the sun wheel center to increase greatly. The research on the influence of the fault factors on the dynamic characteristics of the system provides a theoretical evidence for the fault diagnosis of the planetary gear transmission system.